PERPUSTAKAAN UMUM DAERAH KABUPATEN KUBU RAYA DENGAN PENDEKATAN ARSITEKTUR TROPIS MODERN - Rahmaniawati, Dian Ayu; Andi, Uray Fery; Lestari, Lestari (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Each year, less than 1% of the population visits the Kubu Raya Regency Regional Public Library. This is due to the less strategic location of the library. In addition, the library space does not meet standard space requirements. Due to its geographical location, Kubu Raya Regency is included in a tropical climate with average temperatures and high rainfall. Therefore, a design method that can be adapted to the climate is needed to achieve comfort in the building. The purpose of the design of the Kubu Raya Regency Regional Public Library is to meet the comfort and space needs of the users by applying a modern tropical architectural approach. The design is done through several stages, starting from data collection, analysis, concept synthesis and design. The result of the design is the creation of a library building that is comfortable and can meet the needs of its users. The comfort of the building is achieved through a good lighting and ventilation system by creating an open space in the center of the building, making many openings, applying a cross ventilation system, adding a secondary skin and sun shading. To meet the needs of the user space, it is realized through the provision of space that is adjusted to the results of the analysis of the user space requirements and the standard space requirements for district / city public libraries. The building is rectangular in shape with a pitched roof. The side of the building is covered with a secondary skin of ACP and a sunshade with batik motifs typical of Kubu Raya.